2021
DOI: 10.1021/acsaem.1c00438
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively Designing Porous Copper Current Collectors for Lithium Metal Anodes

Abstract: Lithium metal has been an attractive candidate as a next-generation anode material. Despite its popularity, stability issues of lithium in the liquid electrolyte and the formation of lithium whiskers have kept it from practical use. Three-dimensional (3D) current collectors have been proposed as an effective method to mitigate whisker growth. Although extensive research has been done, the effects of three key parameters of the 3D current collectors, namely, the surface area, the tortuosity factor, and the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…A detailed discussion of the SEM and XPS measurement can be found in the Supporting Information in Figure S5. As previously done in the literature, ,,, both the reservoir and the conventional methods were applied to evaluate their performance and determine the optimal thickness of the coating layer. As shown in Figure a, the prepared samples show different colors due to interference effects in the thin ZnO layers of varying thicknesses.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed discussion of the SEM and XPS measurement can be found in the Supporting Information in Figure S5. As previously done in the literature, ,,, both the reservoir and the conventional methods were applied to evaluate their performance and determine the optimal thickness of the coating layer. As shown in Figure a, the prepared samples show different colors due to interference effects in the thin ZnO layers of varying thicknesses.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Consequently, there has been extensive research into methods to suppress dendrite formation effectively and, thus, improve the safety and cyclic stability of lithium metal batteries. Examples of these methods include (i) the introduction of a 3D current collector [14][15][16] and a 3D host matrix (scaffold) [17][18][19] having a large specic surface area for lithium deposition, which suppresses volume expansion and reduces the local current density; (ii) the in situ formation of ideal SEIs by optimising the electrolyte 20,21 and the inclusion of additives; [22][23][24] (iii) the formation of uniform Li + -ion ow by modifying the inorganic/ organic particles on the separator; 25,26 and (iv) the physical suppression of dendrite growth by enhancing the mechanical strength of the thin lm by coating with an inorganic/organic solid electrolyte 27,28 or a ceramic thin lm. 8,[29][30][31][32][33] In particular, the introduction of an ex situ protective lm on metallic lithium, that is, the introduction of an articial SEI, is a particularly useful method 34 because undesirable side reactions between metallic lithium and the electrolyte, as well as dendrite growth, can be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of planar Cu foils which have been used as the anode CC in LIBs for decades, a homogeneous Li + ion ux is hardly achievable. 15,20 It has been found that the inhomogeneous Li + ion ux distribution could cause non-uniform Li deposition and dendrite growth. 21 The prevailing understanding regarding CC has reached consensus in the literature that the larger the CC surface area the better the ability to effectively reduce local current density, and therefore minimize 'dead Li' formation.…”
Section: Introductionmentioning
confidence: 99%
“…As the CC surface area is not inherently inuenced by one factor, it is important to control other factors such as surface features and surface chemistry. 20 On one hand, the use of 3D host materials brings into additional complexity, as various parameters, such as the material components, dispersion homogeneity, particle size distribution, electrode thickness, and electrode porosity, all contribute to 'dead Li' formation. 14 On the other hand, the use of a 3D Cu CC using widely reported methods (e.g., chemical modication, 27,28 dealloying modication, 29,30 and protective layer modication, 31,32 ) oen neglects the surface chemistry difference and is also lacking the ability to precisely control the surface features and tortuosity.…”
Section: Introductionmentioning
confidence: 99%